Mixed-culture aerobic anoxygenic photosynthetic bacterial consortia reduce nitrate: Core species dynamics, co-interactions and assessment in raw water of reservoirs. (November 2020) - Zhang, Haihan; Wang, Yan; Huang, Tinglin; Liu, Kaiwen; Huang, Xin; Ma, Ben; Li, Nan; Sekar, Raju
Graphical abstract: Highlights: Three consortia of mixed-culture AAPB were isolated from reservoirs. Mixed-culture AAPB had higher nitrate nitrogen removal efficiencies. Communities of AAPB consortia were investigated by pufM gene sequencing. Dynamics and co-interactions of AAPB drive total nitrogen removal. Mixed-culture AAPB showed potential for reservoir water treatment. Abstract: Three consortia of mixed-culture Aerobic Anoxygenic Photosynthetic Bacteria (AAPB) with excellent aerobic denitrifying ability were isolated from drinking water source reservoirs. The results showed that the removal of dissolved organic carbon (DOC) and nitrate nitrogen (NO3 – -N) by mixed-culture AAPB were higher than 90% and 99%, respectively. The Illumina MiSeq sequencing of pufM gene revealed that the dominant genera and their relative abundance changed over the culture periods. Sphingomonas sanxanigenens was the most dominant species observed at 9 h, whereas at 48 h, the most abundant species was Rhodobacter blasticus . A network analysis demonstrated that the co-interactions among the different genera were complex and variable. Mixed-culture AAPB removed more than 30% of NO3 – -N and 25% of DOC from the source water and this study suggests that mixed-culture AAPB can be regarded as a latent denitrifying microbial inoculum in the reservoir raw water treatment.